Efektivitas Penerapan Konvensi MARPOL dalam Menekan Pencemaran Lingkungan Laut - Salsabila, Alifa; Nugraha, Markus Asta Patma (Politeknik Pelayaran Sumatera Barat, 2025)
The International Convention for the Prevention of Pollution from Ships (MARPOL) is a global legal instrument that plays a central role in protecting the marine environment from the impacts of shipping operations. This article aims to analyze the effectiveness of MARPOL implementation both globally and in Indonesia, taking into account institutional, technological, and maritime economic dimensions. The study employs a qualitative descriptive approach supported by secondary data derived from official International Maritime Organization (IMO) documents, Tokyo Memorandum of Understanding (Tokyo MoU) annual reports, scholarly publications, and Indonesian government reports covering the period 2015–2025. The findings indicate that, at the global level, MARPOL has been effective in curbing marine pollution through strengthened monitoring systems, adoption of environmentally friendly shipping technologies, and incentive mechanisms for the maritime industry. Advanced economies such as Japan, the Republic of Korea, and several European states have achieved high levels of compliance owing to cross-sectoral policies and robust financial support. In contrast, MARPOL implementation in Indonesia remains constrained by weak law enforcement, inadequate port reception facilities, and the high costs associated with adopting low-emission technologies. Major obstacles include limited port infrastructure, insufficient crew training on ship waste management, and low environmental awareness within the shipping sector. To optimize MARPOL implementation, the study recommends strategies to strengthen institutional capacity, provide incentives for green technologies, and enhance international cooperation. With these measures, the effectiveness of MARPOL in reducing marine pollution in Indonesia is expected to improve substantially and sustainably.